THE IMPACT OF SELF-CONFIDENCE AND CREATIVITY ON ENTREPRENEURIAL INTENTIONS: THE MEDIATING ROLE OF RISK-TAKING - Ulfah, Maria; Syahrudin, Husni (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This study aims to examine the role of mediating the relationship between the influence of self-confidence, creativity, and risk-taking on entrepreneurial intentions. This study uses PLS-SEM path analysis and quantitative survey. The population consisted of 572 12th-grade vocational students from ten vocational schools in West Kalimantan, Indonesia, chosen via non-probability purposive sampling based on their internship experiences. Participating vocational students are chosen based on their internships in industry, tourism, and other enterprises. The data was obtained using a Likert scale questionnaire and the analysis looked at internal consistency, construct validity, effect size, coefficient of determination, predictive relevance, and path coefficient. Entrepreneurial intentions (EI) are determined by the dominant factor, namely being able to make changes (CR9, λ = 95.40%), and entrepreneurial risks (EI2, λ = 7.30%) are the lowest factor. The ability of the structural model to explain EI is 50.70%, while the creativity variable explains 85.50% (Q² = 0.855) of the phenomena predicted in the field. Furthermore, the mediating role of risk-taking does not increase a significant positive effect on the effect of self-confidence on EI. This conclusion reveals the importance of developing entrepreneurial creativity and entrepreneurial intentions in shaping higher risk-taking behavior in vocational students. Implementing education and training programs that encourage creativity and entrepreneurial intentions can improve students' ability to deal with risks and take innovative steps in entrepreneurship.